1994
DOI: 10.1111/j.1365-2044.1994.tb03519.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of oral omeprazole on the disposition of lignocaine

Abstract: SummaryThe efects of the gastric antisecretory drug, omeprazole. on the disposition of lignocaine were studied in 10 healthy male volunteers in a double-blind, randomised, placebo-controlled, two-period crossover trial. Omeprazole 40 mg or placebo was taken daily for one week before administration of lignocaine I mg.kg-' (3.7 pmol.kg-') given intravenously over 10 min. Venous concentrations of lignocaine and its metabolite monoethylglycinexylidine were measured in plasma with reversed phase liquid chromatograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…These in vitro data might explain the significant increase in plasma levels of omeprazole and lansoprazole during coadministration of clarithromycin. Although CYP3A4 has been shown to be involved in the metabolism of proton pump inhibitors, no clinically relevant drug interactions could be found with numerous other CYP3A4 substrates (Ching et al 1991;Soons et al 1992;Blohme et al 1993;Galbraith and Michnovicz 1993;Noble et al 1994;Tateishi et al 1995) Therefore, a CYP3A4-independent mechanism was proposed for the clarithromycin/proton pump inhibitor interaction (Gustavson et al 1995;Langtry and Wilde 1997). As clarithromycin has been shown to be effective in inhibiting P-glycoprotein function (Wakasugi et al 1998;Wang et al 2000), inhibition of this transporter might contribute to this interaction.…”
Section: Discussionmentioning
confidence: 95%
“…These in vitro data might explain the significant increase in plasma levels of omeprazole and lansoprazole during coadministration of clarithromycin. Although CYP3A4 has been shown to be involved in the metabolism of proton pump inhibitors, no clinically relevant drug interactions could be found with numerous other CYP3A4 substrates (Ching et al 1991;Soons et al 1992;Blohme et al 1993;Galbraith and Michnovicz 1993;Noble et al 1994;Tateishi et al 1995) Therefore, a CYP3A4-independent mechanism was proposed for the clarithromycin/proton pump inhibitor interaction (Gustavson et al 1995;Langtry and Wilde 1997). As clarithromycin has been shown to be effective in inhibiting P-glycoprotein function (Wakasugi et al 1998;Wang et al 2000), inhibition of this transporter might contribute to this interaction.…”
Section: Discussionmentioning
confidence: 95%
“…The inhibitors of CYP2C19 (omeprazole) and CYP2D6 (propafenone) have little if any effect on intravenous lignocaine (Noble et al 1994;Ujhelyi et al 1993). Interestingly, although CYP3A4 is responsible for the formation of monoethylglycinexylidide in vitro, our study group has previously shown that erythromycin and itraconazole, both strong inhibitors of CYP3A4, have practically no effect on the pharmacokinetics of intravenous lignocaine (Isohanni et al 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Omeprazole 20 to 40mg did not influence the metabolism of cyclosporin.I'<'I estradiol,D56] lidocaine, [88] nifedipine l78] or quinidine,lI57] which all are known to be CYP3A4 substrates; confidence in predicting that no other CYP3A4 substrate would be influenced by omeprazole is, therefore, rather high. Neither the biotransformation of prednisone to prednisolone nor the subsequent disposition of prednisolone, which are both potential CYP3A4 substrates, were affected by omeprazole.…”
Section: 6cyp3a4mentioning
confidence: 99%